2018
DOI: 10.1002/anie.201803536
|View full text |Cite
|
Sign up to set email alerts
|

Facile Chemoenzymatic Synthesis of O‐Mannosyl Glycans

Abstract: O Mannosylation is a vital protein modification involved in brain and muscle development whereas the biological relevance of O-mannosyl glycans has remained largely unknown owing to the lack of structurally defined glycoforms. An efficient scaffold synthesis/enzymatic extension (SSEE) strategy was developed to prepare such structures by combining gram-scale convergent chemical syntheses of three scaffolds and strictly controlled sequential enzymatic extension catalyzed by glycosyltransferases. In total, 45 O-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…2a ), we designed three synthetic building blocks, including a versatile protected glycosyl amino acid 7 with C3-OH protected by an acetyl (Ac) group and C4/6-OH masked by a benzylidene acetal, and two monosaccharide Schmidt donors 8 30 and 9 31 . The Fmoc group is introduced to the Ser residue of 7 to facilitate reaction monitoring and product purification 32 . The Ac group on 7 would be selectively removed under mild basic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2a ), we designed three synthetic building blocks, including a versatile protected glycosyl amino acid 7 with C3-OH protected by an acetyl (Ac) group and C4/6-OH masked by a benzylidene acetal, and two monosaccharide Schmidt donors 8 30 and 9 31 . The Fmoc group is introduced to the Ser residue of 7 to facilitate reaction monitoring and product purification 32 . The Ac group on 7 would be selectively removed under mild basic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite maintaining the pH of the reaction below 8.5 during Zemplén deprotection, nearly 50% of Fmoc was lost. Fmoc was therefore quantitavely reintroduced under basic conditions using Fmoc N -hydroxysuccinimide ester before product purification 32 . Core 2 ( 2 ) was obtained with a yield of 77% over the last three steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions generally proceed under mild, aqueous conditions without the need for toxic and harsh organic reagents. Using bio- and/or chemoenzymatic synthesis tools, several natural and engineered glycan libraries have recently been constructed including asymmetric multi-antennary N -glycans (Wang Z. et al, 2013 ), glycosphingolipid glycans (Yu et al, 2016 ), authentic human type N -glycans (Li L. et al, 2015 ; Hamilton et al, 2017 ), O -mannosyl glycans (Meng et al, 2018 ; Wang S. et al, 2018 ), human milk oligosaccharides (HMOs) (Xiao et al, 2016 ; Prudden et al, 2017 ), and tumor-associated antigens (Li P. J. et al, 2019 ; 'T Hart et al, 2019 ). Similar strategies have been adopted for cell-free enzymatic synthesis of glycolipid libraries including those from bacterial (Glover K. et al, 2005 ), animal (Stubs et al, 2010 ), and human origins (Li S. T. et al, 2019 ).…”
Section: Enzyme-mediated In Vitro Technologies Formentioning
confidence: 99%
“…Chemo-enzymatic approaches have been developed for the synthesis of structurally defined glycans in the last two decades (Koeller et al, 2000 ; Blixt and Razi, 2006 ; Boltje et al, 2009 ; Lepenies et al, 2010 ; Palcic, 2011 ; Schmaltz et al, 2011 ). A lot of effort and various synthetic methods have been introduced to make more complex glycans available (Wang et al, 2013 , 2018 ; Chen, 2015 ; Li et al, 2015 ; Shivatare et al, 2016 ; Prudden et al, 2017 ; Zhang et al, 2017 ; Wen et al, 2018 ; Liu et al, 2019 ), and recently, two enzyme-mediated oligosaccharide synthesizers were reported to facilitate the synthetic progress (Zhang et al, 2018 ; Li et al, 2019 ). Despite many recent advancements in prototypic automated glycan synthesis, the synthesis of complex, highly branched glycan structures is still extremely challenging and can only be carried out in a number of noncommercialized laboratories.…”
Section: Introductionmentioning
confidence: 99%